PERAN GURU TERHADAP ANAK PENYANDANG TUNAGRAHITA DITINJAU DARI KINERJA KOMPETENSI GURU (Studi Kasus Sekolah Luar Biasa Negeri Pembina Pekanbaru) - Irfan Tongam S; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Child is a best gift that given by God. But sometimes, there are some children who looks different from children in general, such as tunagrahita children. Tunagrahita is a mental disorder that occurs in a person who has an IQ below average. Some of tunagrahita children have the opportunity to get the same education as children in general, such as studying at Sekolah Luar Biasa(SLB) Negeri Pembina Pekanbaru. The role of teachers for children with disabilities is very important to support the development that occurs to them. So this study aims to Describe the role of teachers in Sekolah Luar Biasa Negeri Pembina Pekanbaru to children with a tunagrahita in accordance with teacher competency standards. The research method used is quantitative method. The theory in this study consists of the theory of stages of socialization by George Herbert Mead, role theory by Glen Elder, and the theory of dramaturgy by Goffman. In this study the number of subjects as many as 27 teachers classroom tunagrahita. Technique of collecting data by observation, documentation, and spreading of questionnaire.The results of this study is to see how the application of the role of teachers in Sekolah Luar Biasa Negeri Pembina Pekanbaru to the development of children tunagrahita both academically and non academic. With the provision of special teaching patterns owned by teachers are expected to make tunagrahita children better in receiving teaching, which tunagrahita children are considered weak to understand something. In addition, teachers are also required to be able to introduce the social world to tunagrahita children so they are able to perform its role well in the community. Here also want to see how teachers are able to establish closeness to tunagrahita children to create a more conducive teaching patterns.Keywords: Teacher-specific teaching patterns, development of tunagrahita children